2007
DOI: 10.1074/jbc.m702612200
|View full text |Cite
|
Sign up to set email alerts
|

Group G Streptococcal IgG Binding Molecules FOG and Protein G Have Different Impacts on Opsonization by C1q

Abstract: Recent epidemiological data on diseases caused by ␤-hemolytic streptococci belonging to Lancefield group C and G (GCS,GGSStreptococci of the Lancefield group G and C (GGS 2 and GCS) have long been considered as animal pathogens, being a minor threat to human carriers. Carriage of GCS and GGS in the throat and on the skin is often asymptomatic. However, reports from different parts of the world are accumulating demonstrating that they are emerging as important human pathogens (1-4). Individual processes contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Thus the approach and binding of such a large molecule as C1q would be compromised, resulting in more complete inhibition of the complement pathway. Support for this notion comes from related studies with protein G. Although one study found soluble streptococcal protein G unable to block both C1q binding to IgG and complementmediated lysis of IgG-sensitized red blood cells (42), another demonstrated that, when IgG is bound by bacterial cell-surface protein G, interaction with C1q is completely blocked (44). The authors of the second study proposed that the presence of protein G in a defined orientation and spacing on the streptococcal cell surface facilitates inhibition of the interaction of C1q with protein G-bound IgG.…”
Section: Discussionmentioning
confidence: 79%
“…Thus the approach and binding of such a large molecule as C1q would be compromised, resulting in more complete inhibition of the complement pathway. Support for this notion comes from related studies with protein G. Although one study found soluble streptococcal protein G unable to block both C1q binding to IgG and complementmediated lysis of IgG-sensitized red blood cells (42), another demonstrated that, when IgG is bound by bacterial cell-surface protein G, interaction with C1q is completely blocked (44). The authors of the second study proposed that the presence of protein G in a defined orientation and spacing on the streptococcal cell surface facilitates inhibition of the interaction of C1q with protein G-bound IgG.…”
Section: Discussionmentioning
confidence: 79%
“…GGS wild-type strain G45 was isolated at the Royal Brisbane Hospital in Brisbane, Australia. Two isogenic mutant strains G45D PG and G45D FOG (Nitsche-Schmitz et al, 2007), lacking protein G or protein FOG, respectively, were also used. Bacteria were grown overnight in ToddHewitt broth (Difco/BD) supplemented with 0.2 % yeast extract (Oxoid) (THY) at 37 uC, in the presence of 5 % CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Two main proteins found on the surface of GGS, protein G and FOG, have been the primary focus of studies regarding bacterial interactions with the human host (Johansson et al, 2004;Nitsche-Schmitz et al, 2007;Egesten et al, 2011). Protein G is the main IgG-binding protein of GGS and exhibits high affinity for IgG from different species (Björck & Kronvall, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococci were routinely grown in Todd Hewitt broth (Difco) containing yeast extract (2 g/liter; Oxoid Ltd.) in 5% CO 2 at 37°C. The isogenic mutants G45⌬FOG and G45⌬G, lacking protein FOG and protein G, respectively, were grown in the presence of erythromycin (1 g/ml) to maintain the knocked out phenotype (32).…”
Section: Methodsmentioning
confidence: 99%